Training Design to Improve Quality of Response: Training to Stimulate Application of Clarity Standard on The Elements of Thinking - Nugraha, Fida Nirmala (ANIMA Indonesian Psychological Journal, 2012)
Critical thinking is a must have cognitive characteristics of first year students that enable them to responds to the problems adequately. On the other hand students are rarely having the chance to develop the ability since they are used to get instant results instead of paying attention on the process (Day, 1981; King, Wood, & Mines, 1990). Training that urged students to implement clarity standard on the elements of thinking can stimulate critical thinking. Using randomized pretest posttest control group design, the training is significantly increasing e quality to solve pro- blem amongst subjects. The experimental group has to solve two ill structured problems: one served as pre and posttest, the other is served as a part of problem based learning which both cases force them to applied clarity standard on the elements of thinking. Control group receive only pre and posttest case. Kemampuan berpikir kritis merupakan salah satu karakteristik perkembangan kognitif yang harus dikuasai mahasiswa agar dapat memberikan respons yang tepat pada saat menyelesai- kan persoalan. Mahasiswa umumnya terbiasa memperoleh hasil secara instan dan kurang memperhatikan proses pencapaian hasil (Day, 1981; King, Wood, & Mines, 1990). Salah satu cara untuk menstimulasi perkembangan kognitif individu dapat dilakukan melalui pelatihan untuk menstimulasi penerapan standar clarity pada elemen berpikir. Dengan desain randomized pretest-posttest control group yang diikuti subjek, pelatihan secara signifikan dapat meningkatkan kualitas respons yang ditampilkan pada saat menyelesaikan persoalan. Kelompok ekspe- rimen harus menyelesaikan dua persoalan yang ambigu (ill structured) yaitu satu persoalan sebagai pretest dan posttest sedangkan persoalan lainnya merupakan implementasi pro- blem based learning yang menuntut subjek kelompok ini untuk menerapkan standar clarity pada elemen-elemen berpikir agar dapat memberikan respons yang tepat.